2019
DOI: 10.32527/2019/101417
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Disorder in Nuclear Receptor Amino Termini: From Investigational Challenge to Therapeutic Opportunity

Abstract: Epidermal keratinocytes form an effective renewable barrier to surface assaults and desiccation of underlying tissues through a tightly controlled program of regeneration and terminal differentiation which is significantly impacted by the activity of several members of the nuclear receptor (NR) superfamily. As such, there is significant interest in physiological and pharmacological control of select NRs. NRs are usually considered quintessential examples of constrained structure-function relationships among pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…A number of studies has shown that the NTD of NRs is not only critical for several aspects of NR action but also can be exploited as drug targets, thereby opening new opportunities for endocrine-based therapies. 266,267 Lack of significant sequence homology between NRs within the NTD also suggests that targeting this domain could give selective modulators of NRs, yielding fewer side effects. Traditional views of structural drug discovery would tend to consider such intrinsically disordered regions as unattractive targets due to their lack of structure and the concomitant lack of binding pockets for small molecules to interact.…”
Section: Importance Of Nr-ntds In Diseases and As Pharmaceutical Targetsmentioning
confidence: 99%
“…A number of studies has shown that the NTD of NRs is not only critical for several aspects of NR action but also can be exploited as drug targets, thereby opening new opportunities for endocrine-based therapies. 266,267 Lack of significant sequence homology between NRs within the NTD also suggests that targeting this domain could give selective modulators of NRs, yielding fewer side effects. Traditional views of structural drug discovery would tend to consider such intrinsically disordered regions as unattractive targets due to their lack of structure and the concomitant lack of binding pockets for small molecules to interact.…”
Section: Importance Of Nr-ntds In Diseases and As Pharmaceutical Targetsmentioning
confidence: 99%
“…Unfortunately, IDRs are frequently under-represented by researchers in favor of more stable and structured regions of proteins. 36 Exploration of IDRs through biophysical techniques, such as nuclear magnetic resonance (NMR) 37 and small-angle X-ray scattering (SAXS), 38 yields significant insights into their dynamic properties, providing information on the average conformational state and the dynamics of IDRs. CryoEM 39 is potentially useful, but limited to singular static structures and cannot capture the inherent dynamic nature of IDRs.…”
Section: Introductionmentioning
confidence: 99%